Statute, ethnic identity and perceived variability in children - Mouro, Carla (2002)
The main purpose of this study was to address the moderator role of the identification level with the ethnic ingroup on the relationship between the ethnic status of the groups and the relative ingroup and outgroup variability in children. Nine to 10 year-old White and Black children distributed white and black faces along four general dimensions used to characterize children in general. The research design was 2 status × 2 identification level × 2 target group. Results showed a main effect of target group: both White and Black children perceived more variability in the white than in the black target group. In addition, a three way interaction showed that Black children's perceptions of variability are influenced by their level of identification while White children's are not. Black children with high identification display an ingroup homogeneity effect and Black children with moderate identification do not differentiate the groups. These results are discussed within the framework of motivational perspectives of perceived variability. DOI: http://dx.doi.org/10.17575/rpsicol.v16i2.485